Influences of Cultures on Open Space Planning for Hanoi City of Vietnam - Liên, Nguyễn Thị Hoàng (VNU Journal of Science: Earth and Environmental Sciences, 2014)
Abstract: During its long history,HanoiCityofVietnamhas experienced many different cultures including Chinese, French, Soviet and other contemporary influences. The question to be addressed in this paper, therefore, is: have different Eastern and Western cultures that have dominated the development ofHanoiCityinfluenced open space planning? The review of the case study showed that the various fragmented historical and cultural periods of influence have generated different approaches to urban planning and provision of open space. In Hanoi, both capitalist and socialist planning approaches have been applied at different periods of time. These differences are still evident in present day of Hanoi City. The study concluded that although representative plans for each historical period highly valued open space, none of these plans met all the evaluation criteria. The analysis also highlighted the limitations of each plan which needed to be considered in order to achieve effective planning. Findings of this study will contribute to the research literature on the fields of planning for liveability and urban open space. They will also help to inform the city government, planners and communities of Hanoi City about issues related to city planning and provision of open space from the past to the present. In this manner, this study makes a contribution towards a “greener” Hanoi in a more liveable capital city. Keywords: City, culture, Hanoi, open space, planning, urban.